STRATEGI KEAMANAN CYBER SECURITY DI KAWASAN ASIA TENGGARA: SELF-HELP ATAU MULTILATERALISM? - Iqbal Ramadhan (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2019)
Cyber security is a new kind of topic in security studies. This issue came as prominent discourse when all the human aspect range from politics, military, economics and societal are connected to the cyber space. Cyber terrorism, cyber crime and cyber war are the most potential threat who come from the cyber world. As the strategic region in the world, South East Asia who has promising economic growth cannot escape from those threats. The aim of this research is to explain what kind of strategy that can be implemented in protecting the cyber security of South East Asia. To answer the research question, the author used mainstream approach such neorealism and neoliberalism. From the author’s perspective, ASEAN countries need to develop their technological power without ignoring the weightiness of interstate cooperation. Keywords: cyber security, neorealism, neoliberalism, security studies, South East Asia Abstrak Keamanan cyber pada hakikatnya merupakan isu dalam studi keamanan yang terbilang masih sangat baru. Isu ini muncul ketika semua aspek kehidupan politik, militer, ekonomi, sosial dan budaya terhubung ke dunia maya. Ancaman cyber yang berpotensi sebagai ancaman adalah cyber terrorism, cyber crime dan cyber war. Asia Tenggara sebagai salah satu kawasan penting di dunia dengan tingkat pertumbuhan ekonomi yang cukup tinggi tidak terlepas dari ancaman tersebut. Penelitian ini bertujuan untuk membahas strategi seperti apakah yang paling tepat dalam menjaga keamanan cyber di kawasan Asia Tenggara. Dalam menjawab research question, peneliti menggunakan pendekatan mainstream seperti neorealism dan neoliberal. Pada intinya, negara yang tergabung sebagai anggota ASEAN perlu mengembangkan kemampuan power teknologinya tanpa mengesampingkan pentingnya kerja sama antar negara. Kata Kunci: keamanan cyber, neorealis, neoliberalis, studi keamanan, Asia Tenggara